Women and inter-organizational boundary spanning: A way into upper management? - Pedro Araújo-Pinzón; Concha Álvarez-Dardet; Juan Manuel Ramón-Jerónimo; Raquel Flórez-López (European Research on Management and Business Economics (ERMBE), 2017)
This study analyses the presence of gender segregation in Spanish exporting firms. Both women's access to managerial positions (vertical segregation) and women's achievement of managerial roles that are socially associated with communal attributes (horizontal segregation) are tested. We argue that boundary-spanning (henceforth, boundary management) in export interfirm relationships benefits from relational and communal skills and therefore could not only offer an opportunity for women to gain access to management positions but also put them at risk of falling into a rut before achieving other controlbased managerial roles. This empirical study examines the characteristics (personal and firm-level) of Spanish female managers in charge of export management through independent channels. A multivariate analysis has been performed to compare female managers with male managers both in boundary management and in the position of finance director, a control position closer to a socially stereotyped masculine role. The results show that women have slightly higher access to boundary management jobs than finance management jobs, as well as a significantly lower promotion time than male colleagues, but they also corroborate that there is a smaller percentage of women than men in any management positions, with female managers working in younger firms with fewer resources for export activity.
Keywords: J16; M10; 650; Gender; Inter-organizational relationships; Boundary management; Externalized export channels; Vertical and horizontal segregation